Atypical Atrioventricular Nodal Reentry Tachycardia with Eccentric Retrograde Left-Sided Activation of Coronary Sinus (Global Journal of Medical Research, 2013)
Background: Recent anatomical and electro-physiological studies demonstrated, that in the human atrioventricular node there are two main extension, rightward and leftward posterior nodal extension (LPNE). The occurrence of eccentric retrograde atrial activation has been demonstrated to be from 6 to 8% in patients with AVNRT by several previous reports. Objectives: The study was performed to confirm that standard right atrium ablation is effective and successful for atrioventricular node reentry tachycardia (AVNRT) with eccentric retrograde left-sided activation, masquerading a tachycardia which look like as a tachycardia using left accessory pathway. Methods and Results: During a 7 years period (from 2002 to 2008), 865 consecutive patients underwent electrophysiological study. In the group with atrioventricular node reentry tachycardia (AVNRT) there were 178 patients. In the group with typical fast-slow AVNRT (162 pts) there was concentric retrograde activation of the both atrium.
Keywords: atypical AVNRT; eccentric retrograde activation; catheter ablation